Fossil Hegemony - About the Relationship betwen Analysis and Strategy in the Climate Movement - Switala, Leon; Anderegg, Caesar (Momentum Quarterly, 2024)
The strategies of many contemporary radical socio-ecological movements bear witness to an incomplete analysis offossil capitalism. Therefore, in a first part, we argue for a more complex understanding of fossil capitalist hegemony that takes into account the materiality and everyday sense in capitalism. Here, we are especially referring to Nancy Fraser’s theory of cannibalistic capitalism and Ulrich Brand and Markus Wissen’s concept of the ‘imperial way of life’. Against this background, in a second step we show the truncated analysis and its reflection in the strategy of two heuristic groups of actors – the left-liberal and anti-capitalist-revolutionary groups of actors. Finally, we draw first conclusions for a more comprehensive radical, climate-political strategy.
Keywords: hegemony; climate; social-ecological movement; capitalism